HLA-DQ alleles in patients with cutaneous leishmaniasis in Sri Lanka: a preliminary report - Samaranayake, T.N.; Balaji, K.; Fernando, S.D.; Jayasekara, R.W.; Dissanayake, V.H.W. (My University, 2012)
Leishmanisis is an endemic disease in Sri Lanka with localized cutaneous leishmaniasis (LCL) continuing to be the predominant form to be reported. L. donovani, the parasite isolated from cutaneous lesions in Sri Lanka, is commonly known to cause the visceral form of the disease, in foci around the world. Polymorphisms of human leucocytes antigen (HLA) system have been implicated in susceptibility as well as the phenotype of leishmaniasis.